Bibliometric analysis of electroencephalogram research in mild cognitive impairment from 2005 to 2022 - Liu, Mingrui; Liu, Baohu; Ye, Zelin; Wu, Dongyu (Frontiers in Neuroscience, 2023)
Background Electroencephalogram (EEG), one of the most commonly used noninvasive neurophysiological examination techniques, advanced rapidly between 2005 and 2022, particularly when it was used for the diagnosis and prognosis of mild cognitive impairment (MCI). This study used a bibliometric approach to synthesize the knowledge structure and cutting-edge hotspots of EEG application in the MCI. Methods Related publications in the Web of Science Core Collection (WosCC) were retrieved from inception to September 30, 2022. CiteSpace, VOSviewer, and HistCite software were employed to perform bibliographic and visualization analyses. Results Between 2005 and 2022, 2,905 studies related to the application of EEG in MCI were investigated. The United States had the highest number of publications and was at the top of the list of international collaborations. In terms of total number of articles, IRCCS San Raffaele Pisana ranked first among institutions. The Clinical Neurophysiology published the greatest number of articles. The author with the highest citations was Babiloni C. In descending order of frequency, keywords with the highest frequency were "EEG," "mild cognitive impairment", and "Alzheimer's disease". Conclusion The application of EEG in MCI was investigated using bibliographic analysis. The research emphasis has shifted from examining local brain lesions with EEG to neural network mechanisms. The paradigm of big data and intelligent analysis is becoming more relevant in EEG analytical methods. The use of EEG to link MCI to other related neurological disorders, and to evaluate new targets for diagnosis and treatment, has become a new research trend. The above-mentioned findings have implications in the future research on the application of EEG in MCI.